PENGARUH PERLAKUAN PEMANASAN PADA ANISOTROPI MAGNETIK SUSEPTIBILITAS DARI BATUAN BEKU - Arifin, Yayu Indriati (Jurnal Sainstek, 2009)
A series of experiment have been done to study effect of heating to anisotropy of magnetic susceptibility (AMS). The series of experiment include measurement of AMS of fresh rocks and after heating treatment. The sample of rocks from Gunung Sekopiah site and Watu Adeg site, Both of sites located in Daerah Istimewa Yogyakarta province. The AMS fabric of SKP site consistent with assumption that rock from this site is dike. This is also confirms that this rock is intrusive one. Heating treatment on the sample at temperature range between 25 300oC doesnt effect on susceptibility of AMS. But the susceptibility of AMS decreases if sample heated at higher temperature.